Biochar application: A sustainable approach to improve soil health - Singh Yadav, Shubh Pravat; Bhandari, Sujan; Bhatta, Dibya; Poudel, Anju; Bhattarai, Susmita; Yadav, Puja; Ghimire, Netra; Paudel, Prava; Paudel, Pragya; Shrestha, Jiban; Oli, Biplov (Journal of agriculture and food research, 2023)
Soil is a fundamental part of successful agriculture, and its quality has to be improved to maximize crop yield and soil fertility. To increase crop productivity and soil fertility, biochar can be applied to the soil. Biochar is a solid carbon-rich product produced from biomass of agricultural crop residues, wastes, and wood, through pyrolysis in an oxygen-deficient condition. Carbon sequestration through biochar is important because of its potential applications in recycling wastes, retaining nutrients in the soil and lowering greenhouse gas emissions. In this review, we explore the various applications of biochar to ensure the safe and sustainable improvement of soil fertility. This review provides an overview of biochar properties, production technology, and its employment in the agriculture. This review would be a useful resource for researchers, farmers, and academics who are interested in the utilization of biochar. [Display omitted] •Biochar use is increasing rapidly for the sustainable production of agricultural goods and to improve soil health.•Woody and dry matter, including agricultural wastes such as straw, husks, and nut shells, are ideal for biochar extraction.•Biochar is crucial for improving soil quality and decreasing greenhouse emissions, thus mitigating global climate change.